Characterization of the Bendability of Press‐Hardened 22MnB5 Steel. Issue 5 (14th January 2014) - Choi, Won Seok; De Cooman, Bruno C.
<x xml:space="preserve">Abstract</x> The bendability of press‐hardened 22MnB5 steel was used as evaluation criterion to assess the ability of a press‐hardened part to deform plastically in side impact crash conditions. The initiation sites of crack initiating shear bands during the bending operation of press‐hardened 22MnB5 steel were found to be formed by surface roughening. Uncoated press‐hardened 22MnB5 steel is subject to decarburization and oxidation phenomena occurring during austenitization. These surface processes were found to have a pronounced influence on the bendability of the steel, but their influence on the tensile properties was negligible. Decarburization has a positive influence on bendability by softening the outer sheet surface. Austenitization times prior to press forming in excess of 10 min, resulted in the formation of a surface oxide layer which suppressed the continuation of the decarburization and resulted in the re‐homogenization of the carbon concentration profile in the subsurface region. As a result, the decarburization layer was gradually removed, and the bendability of the press‐hardened 22MnB5 steel was reduced.